Centeral Electric Field and Threshold Voltage in Accumulation Mode Junctionless Cylindrical Surrounding Gate MOSFET - Hakkee Jung (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Transfer characteristics is presented using analytical potential distribution of accumulation-mode junctionless cylindrical surrounding-gate (JLCSG) MOSFET, and deviation of center electric field at threshold voltage is analyzed for channel length and oxide thickness. Threshold voltages presented in this paper is good agreement with results of other compared papers, and transfer characteristics is agreed with those of two-dimensional simulation. The most important factor to determine threshold voltage is center electric field at source because the greater part of electron flows through center axis of JLCSG MOSFET. As a result of analysis for center electric field at threshold voltage, center electric field is decreased with reduction of channel length due to drain induced barrier lowering. Center electric field is increased with decrease of oxide thickness, and deviation of center electric field for channel length is significantly occurred with decrease of oxide thickness.